Morfofisiologia de mudas de espécies lenhosas submetidas à estímulo hormonal e perturbação mecânica - Braz, Hannah (2020)
Chemical and mechanical stimuli promote morphological alterations, which can improve performance in the field. Moreover, the practicality and the possibility of posterior use of the material used as samples to determine moisture content of the lot bases the investigation of the reliability of the resistive meters, to replace the traditional method. This study aimed to compare destructive and non-destructive methodology in the quantification of the water content in stems of woody species rustified with methyl jasmonate and stem bending, as well as to evaluate the morpho-physiological characteristics during water deficit. Seedlings of Inga sessilis and Nectandra grandiflora were submitted to 20 repetitions of stem bending, pulverization with 50 μmol L-1 of methyl jasmonate, and a control treatment for eight weeks. Subsequently, morphologic aspects were analyzed fortnightly under water deficit for one month, as well as moisture, with resistive apparatus and through gravimetric method. The experimental design was completely randomized, with seven replications of three seedlings. For I. sessilis, both methods indicated lower moisture in the flexed seedlings, in the evaluation at time zero. In fifteen days, both showed similarities between treatments. At 30 days, the lowest moisture levels were observed in the control by both methodologies. For N. grandiflora, the destructive method did not differentiate the treatments at 0 days, and the alternative method presented lower moisture for the stem flexes, not differing from jasmonate. At fifteen days, the treatments did not differ between each other, for both and, at thirty days, the destructive method indicated higher moisture for the flexed seedlings, and the treatments did not differ by the alternative method. In relation to the morpho-physiological characteristics, for N. grandiflora, stem bending yielded lower root emission, and when subjected to water deficit, presented reduced leaf area, leaf dry mass, and increment in height until the end of the period evaluated. For I. sessilis, at time 0 and on the 15th day, the the stem bending resulted in lower leaf dry mass in relation to jasmonate; however, neither one differed from the control. At the15th day, the smallest leaf area was observed in seedlings treated with stem flexes, as well as the lowest loss of electrolytes in the root tissue. At 30th day, both hardening treatments showed lower leaf area and leaf dry mass, and jasmonate showed lower stem and root dry mass in relation to the control treatment. It was not found any relationship that could ensure the veracity in the results yielded by the non-destructive method, disenabling the substitution of the gravimetric method for both species evaluated.